Cost benefit of investment on quality in pharmaceutical manufacturing: WHO GMP pre- and post-certification of a Nigerian pharmaceutical manufacturer - Chimezie Anyakora; Obinna Ekwunife; Faith Alozie; Mopa Esuga; Jonathan Ukwuru; Steve Onya; Jude Nwokike (BMC, 2017)
Abstract Background Pharmaceutical companies in Africa need to invest in both facilities and quality management systems to achieve good manufacturing practice (GMP) compliance. Compliance to international GMP standards is important to the attainment of World Health Organization (WHO) prequalification. However, most of the local pharmaceutical manufacturing companies may be deterred from investing in quality because of many reasons, ranging from financial constraints to technical capacity. This paper primarily evaluates benefits against the cost of investing in GMP, using a Nigerian pharmaceutical company, Chi Pharmaceuticals Limited, as a case study. This paper also discusses how to drive more local manufacturers to invest in quality to attain GMP compliance; and proffers practical recommendations for local manufacturers who would want to invest in quality to meet ethical and regulatory obligations. Method The cost benefit of improving the quality of Chi Pharmaceuticals Limited's facilities and system to attain WHO GMP certification for the production of zinc sulfate 20-mg dispersible tablets was calculated by dividing the annual benefits derived from quality improvement interventions by the annual costs of implementing quality improvement interventions, referred to as a benefit-cost ratio (BCR). Result Cost benefit of obtaining WHO GMP certification for the production of zinc sulfate 20-mg dispersible tablets was 5.3 (95% confidence interval of 5.0-5.5). Conclusion Investment in quality improvement intervention is cost-beneficial for local manufacturing companies. Governments and regulators in African countries should support pharmaceutical companies striving to invest in quality. Collaboration of local manufacturing companies with global companies will further improve quality. Local pharmaceutical companies should be encouraged to key into development opportunities available for pharmaceutical companies in Africa.